2018
DOI: 10.1080/17449359.2018.1465825
|View full text |Cite
|
Sign up to set email alerts
|

Performing Pan American Airways through coloniality: an ANTi-History approach to narratives and business history

Abstract: This paper centers on the role of narratives in business history from an ANTi-History perspective. We focus on the networked processes through which narratives are told of, for and by multinational companies embed the development of 'new imperialism' and coloniality. We set out to achieve this through a discussion and application of ANTi-History to a study of Pan American Airways and particularly its performance as a maturing multinational company and its relationship to postcoloniality. In the process, we als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…A recent example is the rebranding of the Aunt Jemima line of breakfast products by parent company PepsiCo in February 2021 after recognizing that the packaging was “based on a racial stereotype,” given the more recent calls for racial equality (Tyko, 2021). Other discussions in the literature that outline colonial issues in organizations include imperial narratives in the internal discourse of the Hudson’s Bay Company (Smith and Simeone, 2017), Eurocentric influences on the Brazilian advertising self-regulation system (Rodrigues and Hemais, 2020), and the corporate history of Pan Am as it relates to American imperialism (Kivijärvi et al, 2019; Paludi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A recent example is the rebranding of the Aunt Jemima line of breakfast products by parent company PepsiCo in February 2021 after recognizing that the packaging was “based on a racial stereotype,” given the more recent calls for racial equality (Tyko, 2021). Other discussions in the literature that outline colonial issues in organizations include imperial narratives in the internal discourse of the Hudson’s Bay Company (Smith and Simeone, 2017), Eurocentric influences on the Brazilian advertising self-regulation system (Rodrigues and Hemais, 2020), and the corporate history of Pan Am as it relates to American imperialism (Kivijärvi et al, 2019; Paludi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, Durepos and Mills (2012a) and Mills and Durepos (2010: 27) argued that ANTi-History makes apparent the instrumentality of historical accounts enacting transparency in history. Durepos (2015) emphasizes that history is enacted through heterogeneous practices (see Corrigan, 2016) performing history through both human and non-human actants (Durepos and Mills, 2018; Hartt et al, 2014; Latour, 1999; Kivijarvi et al, 2018). If an element participates in the course of action, making a difference in other actors’ actions and leaving behind some detectable trail that allows researchers to identify its presence, it is an actant (Latour, 2005).…”
Section: Anti-historymentioning
confidence: 99%
“…Tracing politics of actor-networks may make explicit silenced but salient voices and untold stories (Durepos et al, 2008; Kivijarvi et al, 2018). Durepos et al (2008) researched an airline’s history and concluded that ‘actors try imputing or imposing interests upon others in hopes of enlisting them onto their cause’ (p. 76).…”
Section: Anti-historymentioning
confidence: 99%
See 2 more Smart Citations